BASE MATERIALS IN THE DESIGN OF MODERN KITCHEN FURNITURE - Абизов, В. А.; Агліуллін, Р. М. (Art and Design, 2020)
The purpose of the article is to analyze the basic materials used in the design of modern cabinet furniture in the kitchen and determine their qualitative and aesthetic gradations.The article applies methods of analysis and synthesis and information processing. The varieties and characteristics of materials for the manufacture of kitchen cabinet furniture of modern apartments from the existing range of materials are analyzed. Materials for the manufacture of kitchen furniture were classified and divided into certain categories, their use in these categories was also determined. It was proposed to classify the materials that are used in the manufacture of kitchen furniture in modern apartments according to qualitative and aesthetic gradation. The criteria for assessing the qualitative and aesthetic gradation of materials are: naturalness and environmental friendliness of materials, reuse of materials, use of innovative technologies and solutions. The cost of the material according to the 100-point system highlighted a definite connection between the high price of the material and its qualitative and aesthetic appearance. One of the main criteria of modern production is the ability to combine materials and the use of materials in original places of structures. The possibility of varying and combining, the use of materials in original places of designs - gives the product uniqueness and competitiveness in the furniture market. A comprehensive analysis of the basic materials used in the design of modern cabinet furniture in the kitchen is carried out and their qualitative and aesthetic gradations, the estimated ball cost of the materials are determined, and options for combining materials are proposed. The results can be used by designers in the design of kitchen cabinet furniture of modern apartments, as well as in their subsequent production. The results of the study give an image of the materials in the design of modern cabinet furniture, and will help not only in professional design, but also in the educational process.